How to Resolve Land Ownership Conflicts Involving Government Assets in Indonesia - Ravi Danendra; Lego Karjoko; Hilaire Tegnan (Contrarius Indonesia, 2026)
This research examines the role of political leadership in shaping land tenure policy and community resistance in Bong Mojo, Surakarta, where a conflict emerged between the Surakarta City Government as the legal holder of land rights and local residents who claimed long term occupation. The research aims to analyze the influence of political leadership on land conflict resolution and to explain how local cultural values reshape the interpretation of land rights. This study applies a sociolegal approach by combining decolonial legal theory, critical legal studies, and critical discourse analysis. The research uses statutory materials, policy documents, field observations, and in-depth interviews with government officials and community representatives to examine the interaction between formal legal institutions and community-based land practices. The findings reveal three principal approaches to resolving land ownership conflicts involving government assets in Indonesia. First, effective conflict resolution requires balancing legal certainty with substantive justice by recognizing the state's authority over public assets while considering the historical occupation, social dependence, and legitimate interests of local communities. Second, participatory governance through dialogue, negotiation, and collaboration among government institutions, affected communities, and other stakeholders provides a more sustainable mechanism for resolving disputes than relying exclusively on formal legal enforcement. Third, integrating statutory land law with local wisdom and the social function of land creates an equitable land governance model that strengthens public trust, protects government assets, promotes social justice, and prevents recurring land conflicts. These findings demonstrate that sustainable land conflict resolution depends on combining legal, institutional, and socio-cultural approaches within a comprehensive governance framework.